A Single Bout of Fatiguing Aerobic Exercise Induces Similar Pronounced Immunological Responses in Both Sexes - Lobo, Lázaro Fernandes; Morais, Mariana Gomes de; Marcucci-Barbosa, Lucas Soares; Martins-Junior, Francisco de Assis Dias; Avelar, Luíza Martino; Vieira, Erica Leandro Marciano; Aidar, Felipe J.; Wanner, Samuel Penna; Silva, Lucélia Scarabeli; Noman, Maria Clara; Camargos, Bruno Muzzi; Freitas, Kátia Michelle; et al. (Frontiers in Physiology, 2022)
Introduction: Skeletal muscle tissue produces, and releases mediators called myokines. These mediators serve several tissues to promote physiological, structural, and immunological changes. However, little is known regarding the relationship between muscle mass and the magnitude of mediators released in the bloodstream in response to exercise. Objective: This study investigated the effects of aerobically fatiguing exercise in healthy, well-trained male and female volunteers and compared exercise-induced changes between sexes. Methods: This study included 18 female and 15 male volunteers in this study. Each participant visited the laboratory on four consecutive days. The first visit consisted of medical history-taking and explanation of the study design. On the second visit, the participants were subjected to maximal capacity running of exercise that was required to prescribe the intensity of the fatiguing exercise. This exercise protocol and whole blood data collection were conducted on the third visit. Blood samples were collected before, immediately, and 1 h after the race protocol. Finally, on the fourth visit, the participants underwent physical evaluations to measure their body composition using dual-energy X-ray absorptiometry (DXA) imaging. Results: The average ages of the male and female groups were 30.5 ± 4.3 years and 34.2 ± 3.7 years, respectively. The female group ran 57 ± 27, while the male group ran 52 ± 15 min until fatigue. In the male and female groups, between pre-test and post-test, the heart rate, the rate of perceived exertion (RPE), the lactate and the creatine kinase (CK) plasmatic levels increased. In the female group, between pre-test and post-test, an increase in total leukocytes, neutrophils, lymphocytes, monocytes, and basophils. The male group also showed an increase in the total leukocytes, neutrophils, lymphocytes and monocytes count increased from pre-test to post-test. In the male and female groups, the fatiguing exercise protocol increased the interleukin (IL)-6 and interleukin (IL)-10. Conclusion: The aerobically fatiguing exercise protocol induced pronounced changes in the total leukocyte count, especially neutrophil and lymphocyte numbers. The protocol also changed the plasma levels of the cytokines IL-6 and IL-10 in both female and male groups.